Tantangan & Peluang Eksistensi Kepemimpinan Ondoafi dalam bingkai Tata Kelola Pemerintahan Kampung Nafri - Awi, Robby K; Silo, Akbar; Torobi, Renida J.; Muhdiarta, Untung (JURNAL EKOLOGI BIROKRASI, 2025)
This study aims to examine the challenges and opportunities for the existence of Ondoafi traditional leadership in the context of governance in Kampung Nafri, Jayapura City, which is experiencing the dynamics of pluralism between traditional power and modern government structures. The main focus is on how Ondoafi leadership maintains its legitimacy and role amid modernization, national regulations, and changes in local social values. This study employs a descriptive qualitative approach using case study methodology, deemed most relevant for understanding complex social phenomena. Data collection techniques include field observations, in-depth interviews with key informants, and documentary analysis. Data analysis is conducted using an inductive-thematic approach with an interactive methodology emphasizing reflective interpretation of the social and historical context. The results of the study show that the existence of Ondoafi faces structural and cultural challenges, such as weak regeneration, the absence of formal regulations, and the marginalization of the role of customs in village development planning. However, great opportunities are also opening up through constitutional recognition of indigenous peoples, support for Papua's special autonomy, and increasing public awareness of the importance of preserving traditional values. Synergy big77 between traditional and formal leadership can be achieved through collaborative governance, the revitalization of traditional institutions, and the participation of Ondoafi in the formulation of village policies. This study recommends an inclusive and responsive village governance model that addresses the social and cultural dynamics of Papua.